Total knee replacement in osteoarthritis and rheumatoid arthritis. - Kaltsas, D S (1985)
Between 1974 and 1983, 187 total knee replacements were performed in 163 patients at four East Kent district general hospitals. With few exceptions pain was the most common indication for the operation and it produced complete or almost complete relief in 90% of cases. The most frequently used prostheses were the Attenborough, Stanmore and Geomedic.